2006
DOI: 10.1007/s10802-005-9006-7
|View full text |Cite
|
Sign up to set email alerts
|

Examining the State-Trait Anxiety Relationship: A Behavioural Genetic Approach

Abstract: State and trait anxiety define different aspects of anxiety, and may represent environmentally and genetically mediated components of this phenotype. Furthermore their relationship, where trait anxiety is expressed through levels of state anxiety under threatening circumstances, may represent a process of interplay between a genetic vulnerability factor and an environmental stressor. To test these hypotheses, we explored genetic and environmental influences on measures of state and trait anxiety in a sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
58
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 35 publications
8
58
2
Order By: Relevance
“…This pattern of results has since been largely replicated in another study of 497 pairs of both male and female twins aged 8-16 years. This study additionally demonstrated that the co-occurrence between state and trait anxiety was mainly due to non-shared environmental factors-although genetic and shared environmental factors also played a role (Lau, Eley, & Stevenson, 2006).…”
Section: Anxiety: State Vs Traitmentioning
confidence: 52%
“…This pattern of results has since been largely replicated in another study of 497 pairs of both male and female twins aged 8-16 years. This study additionally demonstrated that the co-occurrence between state and trait anxiety was mainly due to non-shared environmental factors-although genetic and shared environmental factors also played a role (Lau, Eley, & Stevenson, 2006).…”
Section: Anxiety: State Vs Traitmentioning
confidence: 52%
“…Therefore, it is possible that the assessment of trait anxiety may be influenced by state anxiety and that anxiety state may be influenced by circumstances. This interaction between state and trait anxiety and situations may lead to a low estimation of heritability (Lau et al, 2006). Future work should therefore include studies designed to evaluate gender-specific validity of the AUDIT and the STAI scores and also exclude possible interaction between state and trait anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…State anxiety is primarily environmentally influenced, while trait anxiety reveals a roughly equal contribution of genetic and non-shared environmental factors (Lau et al, 2006;Legrand et al, 1999). As state and trait anxiety are distinct, the relationships between state anxiety or trait anxiety and AUD, with regard to genetic and environmental contributions, may be different.…”
mentioning
confidence: 99%
“…In addition, since we did not find higher state-anxiety levels, having a child with ADHD did not necessarily result in higher anxiety levels. Lau et al (24) suggested that state-anxiety was highly influenced by environmental issues whereas trait-anxiety was particularly influenced by genetics and by the environmental issues that were not common among first-degree relatives. Because only lifetime anxiety symptoms (trait-anxiety) were discrepant between the mothers' groups, our results might suggest that higher levels of anxiety among mothers might not be specifically related to current environmental stressors (i.e., offspring behavior and its consequences in school, familial, and social environments).…”
Section: Discussionmentioning
confidence: 99%